Low Economic Level and the Risk of Overweight Among Indonesian Junior and Senior High School Students - Nugroho, Ariyanto; Setiyo Nugroho, Purwo; Yudhana, Amarin; Sunarti, Sri (UI Scholars Hub, 2025)
Overweight and obesity among Indonesian adolescents have emerged as a pressing public health issue, reflecting global trends. This study examines the relationship between economic status and overweight prevalence among junior and senior high school students in Indonesia, using secondary data from the Global School-based Health Survey (GSHS). This study analyzed data from 9,977 students aged 11–18 years through a cross-sectional design and binary logistic regression, adjusting for dietary habits, physical activity, and sedentary behavior. Overall, 14.7% of students were overweight; the prevalence was notably higher among low-income students (27.4%) compared to high-income groups (14.2%). Students from lower economic backgrounds were 1.374 times more likely to be overweight (95% confidence Interval (CI): 1.011–1.867). Although many reported healthy behaviors, including regular fruit and vegetable consumption and participation in physical education, sedentary lifestyles and limited access to nutritious food remained significant challenges for low-income adolescents. These results highlight the complex interplay between economic status, health behaviors, and environmental factors, highlighting the need for targeted, equity-focused interventions to address disparities and curb obesity in Indonesia’s youth.